Use of Modern Tools in the Formation of Strategic Goals of the Institution of Higher Education - Verbovska, Lesya (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article examines the issue of the development of a higher education institution in conditions of change. A comparative analysis of the development strategies of four higher education institutions was carried out. The expediency of using SWOT analysis in the process of elaborating development and internationalisation strategies is substantiated. The SWOT analysis of domestic universities is provided, and the main results of the research in the field of international activities are presented. It is shown that the strategic process for universities is a rather effective and necessary tool for attracting stakeholders, the ability to take into account global trends in the development of higher education in modern conditions of change. It is shown that in the modern conditions of global changes the issues of formation and achievement of strategic goals are of particular importance for higher education institutions. For example, the priority “Creation of a favourable environment for attracting investments” is not a matter for the university alone, as this process requires the coordinated work of institutions and business entities. It was noted that it is important to take into account and coordinate the actions of all stakeholders, as they are the main agents of change, serving or ensuring the implementation of the necessary changes. A comparative analysis of the strategies of four universities made it possible to identify their strategic goals, mission and directions of development. The study showed that two universities used the SWO T analysis tool to describe the strategy, and opportunities for further development were identified. At the same time, we can say that the goals and priorities of the analysed universities are in line with the Sustainable Development Goals. The necessity to develop a strategy for the development of the higher education institution in terms of the internationalisation strategy with the use of SWOT analysis is substantiated.